2015
DOI: 10.18632/oncotarget.4716
|View full text |Cite
|
Sign up to set email alerts
|

Contact-dependent carcinoma aggregate dispersion by M2a macrophages via ICAM-1 and β2 integrin interactions

Abstract: Tumor-associated macrophages (TAMs) can constitute up to 50% of the tumor mass and have strong implications in tumor progression and metastasis. Macrophages are plastic and can polarize to various subtypes that differ in terms of surface receptor expression as well as cytokine and chemokine production and effector function. Conventionally, macrophages are grouped into two major subtypes: the classically activated M1 macrophages and the alternatively activated M2 macrophages. M1 macrophages are pro-inflammatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
82
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 100 publications
(86 citation statements)
references
References 55 publications
4
82
0
Order By: Relevance
“…The detailed design and fabrication procedure of the poly(dimethylsiloxane) (PDMS) device (Figure 1), comprising a gel region with adjoining media channels separated from the gel channel by trapezoidal posts (100 μm spacing) was tested and validated in our previous publications (16,29,30). The height of the microfluidic channels is 120 μm, the culture media channel width is 500 μm, and the gel region width is 1 mm.…”
Section: Chip Design and Fabricationmentioning
confidence: 99%
“…The detailed design and fabrication procedure of the poly(dimethylsiloxane) (PDMS) device (Figure 1), comprising a gel region with adjoining media channels separated from the gel channel by trapezoidal posts (100 μm spacing) was tested and validated in our previous publications (16,29,30). The height of the microfluidic channels is 120 μm, the culture media channel width is 500 μm, and the gel region width is 1 mm.…”
Section: Chip Design and Fabricationmentioning
confidence: 99%
“…3 consisting of a central gel channel flanked by two fluidic channels was utilized. Similar microfluidic platforms have been used for investigating angiogenesis, 13,14 EMT, 15,16 cancer cell-macrophage interactions, 17 intravasation 18 and extravasation. 19,20 For the present work, GFPexpressing HUVECs were seeded into one of the fluidic channels to form a uniform monolayer mimicking a blood vessel wall (Fig.…”
Section: Pro-metastatic Capabilities Of Tamsmentioning
confidence: 99%
“…The metastasis-promoting effect of macrophages is exerted through cytokine secretion such as TGFß [23]. In an in vitro model of EMT, it was shown that M2-type macrophages in direct contact with carcinoma cells facilitated the dispersion of the latter via ICAM-1 and integrin CD18 interaction [26]. Similarly, in a mouse ovarian cancer model, the initial steps of spheroid formation and transcoelomic metastasis were facilitated by the attachment of cancer cells to macrophages via CD11b/CD18 -ICAM-1 adhesion [25].…”
Section: Lfa-1 Participates In the Cytotoxic Immune Response Against mentioning
confidence: 99%